Wczesne schematy nieadaptacyjne jako predyktory inteligencji emocjonalnej osób dorosłych - Karbowski, Mariusz G.; Łukomski, Bartosz K. (Kultura-Społeczeństwo-Edukacja, 2023)
The aim of the research was an attempt to capture the influence of Early Maladaptive Schemas and it’s connection to Emotional Intelligence in the population of adults between age 18 and 54. After some hypotheses were made, it became clear that they all go down to making the Early Maladaptive Schemas as a really impactful tool in the process of emerging and shaping emotional intelligence. This also draws our attention to how important this might be and how having multiple and intense Early Maladaptive Schemas (EMS) can impact the way we perceive the world around us and how do we look at ourselves. During the research process of this study the data was collected by electronic devices. 102 people took part in the research (68 females and 34 males). To measure occurrence, intensification and quantity of maladaptive schemas areas The Young Schema Questionnaire YSQ-S3-PL, second version in Polish translation by Justyna Oettingen, Jan Chodkiewicz, Dorota Mącik and Ewa Gruszczyńska (2018) was used. In order to take possession of Emotional Intelligence data, Emotional Intelligence Questionnaire in Polish adaptation by Anna Ciechanowicz, Aleksandra Jaworowska, Anna Matczak (2000) played a major role. After gathering and analyzing data conclusion was made that in deed Early Maladaptive Schemas have a moderate negative connection with Emotional Intelligence. Results suggest that high EMS values comes with low EI levels. The more and intense EMS get, the less a person can manage their own emotions in positive ways to effectively reduce stress and use EI to improve thinking and functioning to overcome challenges. However there is no indication of statistically significant correlations between high levels of EMS and the emotional recognition abilities.